GE_GERICHTE C/18577/2014 vom 12. Mai 2017 - GE Cour de justice (2017)
DÉFAUT DE LA CHOSE ; EXÉCUTION PAR ÉQUIVALENT(DROIT PRIVÉ) ; PRINCIPE D'ALLÉGATION ; FARDEAU DE LA PREUVE | CC.8; CPC.157; CO.366.2;